Climatic Changes in the Irrigated Tracts of Indira Gandhi Canal Region of Arid Western Rajasthan, India - Rao, A S (Annals of Arid Zone, 2016)
The climatic changes at three selected locations. along the Indira Gandhi canal region, were studied using the records of annual rainfall (1926-93) and air temperature (1950-93). Though. Ganganagar region has been imposed with canal irrigation since the past around six decades, the increase in annual rainfall was apparent only during the last three decades (1%1-93). The long term rate of increase in the annual rainfall of Ganganagar was 1.029 mm year-1. However. in thc areas where irrigation has bccn imposed during the past two decades like Bikaner and recently at .Jaisalmer, the irrigation effect on rainfall was not observed. In general. decrease in the air temperatures was observed in the region at a rate of 0.0390C year-1 at Ganganagar. 0.023Â°C year-1 at Bikaner and O.009Â°C year-1 at .Jaisalmer.